DATA VISUALIZATION OF INTERNET USAGE IN THE JABODETABEK AREA - Madyatmadja, Evaristus Didik; Nuramalia, An Nisa’a; Kusumawati, Lusi; Jamil, Syahlaa Perdina; Kusumawardhana, Wahyu (ISTEK WIDURI, 2021)
The purpose of this study is to analyze and visualize internet usage data in the Jabodetabek area for the last 3 years, namely 2017, 2018, 2019 using quantitative methods which will display data per city and per year which is processed into the percentage of internet usage in the area. In addition, we also used the K-means clustering method as a method of grouping data and we chose to use the age variable for analysis. Along with the development of information technology, governments in various regions have also begun to expand the circulation of the internet to broaden people's insights and disseminate information more easily. However, in the current situation and conditions, it is felt that the distribution of internet use, especially in the Jabodetabek area, is still not optimal. Even though the area is a metropolitan city as the center of urban community activity. Therefore, through data on the percentage of Jabodetabek areas that access the internet, it can be seen as one of the factors for the government to be able to increase the performance of the internet evenly. The data will be visualized using the Tableau application in graphical form to facilitate information delivery to users in reading the results of data analysis.